Neonatal handling induces deficits in infant mother preference and adult partner preference. Issue 5 (29th May 2012) - Raineki, Charlis; Lutz, Maiara Lenise; Sebben, Vanise; Ribeiro, Rosane Aparecida; Lucion, Aldo Bolten
Abstract Neonatal handling is an experimental procedure used to understand how early‐life adversity can negatively affect neurobehavioral development and place animals on a pathway to pathology. Decreased preference for the maternal odor during infancy is one of many behavioral deficits induced by neonatal handling. Here, we hypothesize that deficits in maternal odor preference may interfere with partner preference in the adult. To test this hypothesis, we assessed infant maternal odor preference and adult partner preference in different reproductive stages in both male and female rats that received neonatal handling. Our results indicate that only neonatally handled females present deficits in maternal odor preference during infancy, but both male and females present deficits in adult partner preference. However, sexual experience was effective in rescuing partner preference deficits in males. These results indicate that, considering infant and adult social interactions, females are more susceptible to the effects of neonatal handling than males. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 496–507, 2013